2019
DOI: 10.1002/htj.21570
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of building envelope using passive cooling techniques to reduce the cooling load in hot‐dry regions

Abstract: In developed countries, the buildings are responsible for massive energy consumption. When the construction is based on the use of nonsustainable methods, the buildings were dependent on the active systems, for ensuring a maximal indoor comfort. This has increased energy consumption and related greenhouse gas emissions. In this study, a reduction technique of cooling load and power consumption in buildings is proposed.This technique involves the combination of three passive cooling techniques, thermal insulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…When they compared their results to those of other cases without PCM, they discovered an (11-25 %) decrease in cooling load. Hussein [2] proposed a method that combines three passive cooling methods: thermal insulation, phase change materials (PCMs), and photovoltaic double glazing. Simulations were carried out using the designbuilder software to determine the most effective proposed strategies among 16 cases.…”
Section: Introductionmentioning
confidence: 99%
“…When they compared their results to those of other cases without PCM, they discovered an (11-25 %) decrease in cooling load. Hussein [2] proposed a method that combines three passive cooling methods: thermal insulation, phase change materials (PCMs), and photovoltaic double glazing. Simulations were carried out using the designbuilder software to determine the most effective proposed strategies among 16 cases.…”
Section: Introductionmentioning
confidence: 99%
“…Many kinds of thermal insulating materials are used for the optimal heat transfer and thermal accumulation through outside walls of buildings with regard to the climate conditions of their location [6]. Phase change materials (PCMs) have become very popular materials for both active [7][8][9][10][11][12][13][14] and passive heating and cooling of buildings [9,10,13,[15][16][17][18], and the research related to this topic is increasing, as shown in Figure 1a [19].…”
Section: Introductionmentioning
confidence: 99%